Fraud in Trade Measurements and Weights from the Perspective of Sharia Economic Law - Siregar, Pani Akhiruddin; Liana, Sufitri; Suryani, Suryani (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
Buying and selling transactions constitute an essential part of daily economic activities in Muslim societies and are fundamentally governed by the principles of muʿāmalāt in Islamic law. Despite clear Qur’anic injunctions and prophetic traditions that command honesty and fairness, fraudulent practices such as reducing measurements and weights continue to occur and harm consumers. This study examines the practice of measurement and weight fraud by sellers and analyzes its legal and ethical implications from the perspective of Islamic economic law. The research employs a qualitative method using a normative legal approach, relying on library research that draws upon primary Islamic legal sources, including the Qur’an and Hadith, classical fiqh literature, as well as secondary sources such as scholarly works on Islamic economic law and Law Number 8 of 1999 on Consumer Protection. The data are analyzed descriptively and conceptually to identify the legal norms and principles governing honesty in trade. The findings demonstrate that reducing measurements and weights constitutes a form of fraud that violates the principles of muʿāmalāt, particularly honesty (ṣidq), trustworthiness (amānah), justice (ʿadl), and mutual consent (tarāḍī). Such practices infringe upon the protection of property rights (ḥifẓ al-māl), distort market fairness, and undermine consumer trust. This study concludes that honesty in measurements and weights is not merely an ethical virtue but a binding legal obligation in Islamic economic law, requiring legal firmness and ethical reform to ensure justice, social trust, and sustainable welfare in commercial life.Keywords: buying and selling; fraud in measurements; honesty principle; consumer protection; Islamic economic law.